Rotâmeros de [2]rotaxanos: estudo do efeito do macrociclo sobre o eixo molecular - Orlando, Tainára (2017)
This work presents the synthesis of three new threads and three new [2]rotaxanes models that have asymmetric stopprs, which allows rotamers to be obtained. The synthesis of the [2]rotaxanes was performed by clipping reaction, where yields were obtained between 22-58%. The rotamers formed were quantified in solution (by 1H NMR spectroscopy) and by theoretical calculations, with the Gibbs free energy was obteined by the optimization of the structures. What can be observed is that the existence of the macrocycle around the thread causes changes in the ratio of rotamers. These changes can be explained by the different intramolecular interactions in the mechanically interlocked molecular. Topological and energetic approach provides information on the contact surface area, interactions energy and paths of interaction intramolecular and intermolecular. Experiments to obtain rotational barrier energy in [2]rotaxanes were carried showing different values for each rotamer of [2]rotaxanes studied. The conformational population and the pirouetting barrier of [2]rotaxanes were correlated with the intramolecular interaction paths, showing that for the [2]rotaxanes synthesized in this work the CH···π type interactions contribute significantly to the estabilization energy and pirouetting barrier. Furthermore, crystallization mechanisms were proposed for the threads and [2]rotaxanes of this work.